Studies in Asian Nervilia (Nervilieae, Epidendroideae, Orchidaceae) IV: N. umphangensis, a new species from the Thai–Myanmar border - Gale, Stephan W.; Rueangruea, Sukid; Suddee, Somran (Phytotaxa, 2014)
The Old World terrestrial orchid genus Nervilia Commerson ex Gaudichaud-Beaupré in Freycinet (1829: 421, t. 35) remains poorly known, especially in Asia. It is diagnosed by its hysteranthous habit, in which a single, terminal, one–several-flowered inflorescence and a single ovate to cordate leaf emerge in succession from a single globose tuber. This temporal separation of flowers and leaves makes complete herbarium collections rare. Some species have been described only from flowers, others have been recorded only from leaves, and occasionally the two are mismatched on the same herbarium sheet. The situation is compounded by the ephemeral nature of the plants; the flowering phase is brief, fructification is rapid with fruit set usually occurring prior to leaf flush, and all above-ground parts die back at the end of the growing season, making plants difficult to locate in the field and under-represented in herbaria. Accordingly, species circumscriptions are often inadequate, vague and sometimes overlapping, and the loss or concealment of potentially useful characters (e.g. leaf coloration, lip indumentum) in dried herbarium (especially type) material challenges their critical re-evaluation.